2022
DOI: 10.1097/md.0000000000028839
|View full text |Cite
|
Sign up to set email alerts
|

Are COVID-19 mRNA vaccine side effects severe enough to cause missed work? Cross-sectional study of health care-associated workers

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome-coronavirus-2, has claimed 5,587,549 lives worldwide as of January 20, 2022. Fortunately, large-scale vaccination can mitigate the impact of COVID-19 by making the disease milder and less common. Although 75.2% of the United States population has received at least 1 dose of a COVID-19 vaccines thus far, concerns regarding vaccine side effects have contributed to vaccine hesitancy. Furthermore, nearly 50% of adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In this study, a higher frequency of COVID-19 vaccine-related adverse symptoms, such as general fatigue, headache, chills, and fever, in females compared to that in males was identified. This was consistent with previous cross-sectional studies ( 15 , 16 ). Moreover, our longitudinal analyses identified longer recovery from side effects in females compared to that in males after each vaccine dose.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, a higher frequency of COVID-19 vaccine-related adverse symptoms, such as general fatigue, headache, chills, and fever, in females compared to that in males was identified. This was consistent with previous cross-sectional studies ( 15 , 16 ). Moreover, our longitudinal analyses identified longer recovery from side effects in females compared to that in males after each vaccine dose.…”
Section: Discussionsupporting
confidence: 94%
“…Several other studies also reported that mRNA COVID-19 vaccines have had side effects that have prompted many to limit daily activities or miss work post-vaccination ( 20 , 21 , 36 ). Similar to the results reported here on vaccine types, Cohen et al found a significant difference in the proportion of those who reported needing to miss work after the second dose, with 49.4% of those who received the higher dose mRNA-1273 vaccine needing to miss work, versus 26.2% of those who received BNT162b2 ( 37 ).…”
Section: Discussionsupporting
confidence: 82%
“…Moderna as mRNA vaccine was determined as its effectivity to prevent infection reach 94.1% ( 5 ). It was reported in earlier study, adverse event of Moderna such as pain, oedema, redness, or rash around injection site or systemic symptom like fever and chills ( 6 ). These consequences could disturb the workers and caused missed work ( 6 ).…”
Section: Introductionmentioning
confidence: 91%